Morphometric Magnetic Resonance Imaging Study in Children With Primary Monosymptomatic Nocturnal Enuresis - Wang, Mengxing; Zhang, Anyi; Zhang, Jilei; Lu, Haifeng; Xu, Shuai; Qin, Zhaoxia; Ma, Jun; Du, Xiaoxia (Frontiers in Pediatrics, 2018)
Abstract Objective: Primary monosymptomatic nocturnal enuresis (PMNE) refers to bed-wetting in children who have no other lower urinary tract symptoms and are never dry for more than 6 months. Our previous studies demonstrated that children with PMNE exhibited brain functional abnormalities compared with healthy controls; however, researches on the abnormalities in gray matter were limited. This study aimed to investigate brain structural changes in gray matter of children with PMNE using magnetic resonance imaging (MRI). Methods: Gray matter volumes (GMVs) and gyrification indices (GIs) were calculated using voxel-based and surface-based morphometry analyses of structural MRI data acquired from 26 children with PMNE and 28 healthy children. To identify between-group differences in gray matter, two-sample t-tests were conducted on GMV and GI images separately. Results: Compared with the controls, children with PMNE showed significantly increased GMVs in the supplementary motor area and medial prefrontal cortex regions (mean GMV in PMNE: 0.54 ± 0.07 liters; mean GMV in controls: 0.50 ± 0.06 liters) and reduced GIs in the right precuneus (mean GI in PMNE: 25.74º ± 2.34º; mean GI in controls: 27.97º ± 1.79º). Conclusion: Children with PMNE showed abnormal GMVs in frontal lobe and GIs in precuneus, and these changes might be involved in the pathological mechanism of PMNE.